Effects of low dietary calcium and lipopolysaccharide challenges on production performance, eggshell quality, and bone metabolism of laying hens - Li, Xin; Uyanga, Victoria Anthony; Jiao, Hongchao; Wang, Xiaojuan; Zhao, Jingpeng; Zhou, Yunlei; Li, Haifang; Lin, Hai (Frontiers in Physiology, 2024)
Dietary calcium supply is essential for bone development and egg production in laying hens. This study investigated the effects of low dietary calcium and lipopolysaccharide (LPS) induced immune challenge in aged laying hens. A total of thirty-two Hy-Line Brown laying hens at 80 weeks old with an average laying rate of 62% were randomly divided into two groups and fed a normal calcium diet (3.57% Ca, NCA) or low calcium diet (2.08% Ca, LCA). At 88 weeks, the experiment was designed using a 2 x 2 factorial arrangement, and hens were intraperitoneally injected with saline (SAL) or LPS (0.5mg/kg, 0.5mg/kg, or 1.5mg/kg body weight) once every 48 h intervals over 5 days. Production performance, egg quality, and bone physiology were evaluated. Results showed that LPS challenge decreased the hen-day egg production, egg mass, and eggshell traits (P < 0.05), but increased (P < 0.05) the calcium content of the tibia compared to SAL-injected hens. LCA diet decreased (P < 0.05) the hen-day egg production, and eggshell traits such as weight, percentage, strength, and thickness compared to the NCA diet. LCA diet increased the serum alkaline phosphatase (ALP) activity (P < 0.01) and tibial expression of ALP (P < 0.05) compared to NCA diet. LPS injection suppressed both the serum ALP activity (P < 0.05) and tibial expression of ALP (P < 0.001) compared to SAL injection. Furthermore, LPS injection increased (P < 0.05) the expression of both pro and anti-inflammatory cytokines in the spleen and tibia. The expression of cathepsin K (Cts K) and matrix metalloproteinase 9 (MMP-9) were downregulated by LPS injection (P < 0.001). Broken and shell-less egg production and calcium content of eggshell, as well as tibial mRNA expression of osteocalcin (Ocn), tumor necrosis factor-alpha (TNF-α) and tartrate-resistant acid phosphatase (TRAP) were affected by the interaction (P < 0.05) of diet and injection. Therefore, this study demonstrated that to certain extents, low dietary calcium and LPS challenge dysregulated bone homeostasis and metabolism, with detrimental effects on the performance and eggshell quality of aged laying hens.